2019
DOI: 10.3390/nu11030509
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy as a Risk Factor for Chronic Kidney Disease Progression: A Multicenter Case–Control Study in Taiwan

Abstract: It has rarely been studied whether the presence and severity of diabetic retinopathy (DR) could influence the renal disease progression among all chronic kidney disease (CKD) diabetic patients. This study investigates the characteristics of diabetic patients, with different stages of chronic kidney disease (CKD), according to the occurrence of diabetic retinopathy and determines the influence of retinopathy in the deterioration of renal function. We conduct a multicenter, longitudinal cohort study based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
2
25
1
Order By: Relevance
“…There were significant differences in DR severity, age, uric acid, albumin and more hypertension events than in other studies [8,23,24]. Patients with DR had a worse baseline eGFR, worse glycemic control (higher HbA1c) and higher uric acid.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…There were significant differences in DR severity, age, uric acid, albumin and more hypertension events than in other studies [8,23,24]. Patients with DR had a worse baseline eGFR, worse glycemic control (higher HbA1c) and higher uric acid.…”
Section: Discussionmentioning
confidence: 57%
“…Our study cohort included all CKD stages. A previous study found that DR is significantly correlated with CKD progression in later CKD stages [8]. This may be because the association between DR severity and ESRD events was weaker than for the baseline CKD stage.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, another study reported association of ratio of glycated albumin to HbA1c, an indicator reflecting fluctuations in plasma glucose, with DR but not with DN [34]. Although controversies remain, a relationship between DR and kidney function has been identified [35,36]. Comorbidity of DR and DN is common in diabetic patients; the two entities have a similar pathogenesis, including endothelial dysfunction, thickened basement membrane, and/or chronic inflammation [37].…”
Section: Discussionmentioning
confidence: 99%